Unidirectional photoinduced shuttling in a rotaxane with a symmetric stilbene dumbbell - Stanier, C; Alderman, S; Claridge, T; Anderson, H (2002)
Up and down the dumbbell: Photoisomerization of a stilbene rotaxane results in relocation of the cyclodextrin macrocycle in just one direction (see scheme). This behavior, and that of related rotaxanes, sheds light on the mechanism of shuttling in molecular machines.